Relativistic and Quantum Revisions of the Multisource Thermal Model in High-Energy Collisions - Fu-Hu Liu; Cai-Xing Tian; Mai-Ying Duan; Bao-Chun Li (Advances in High Energy Physics)
The multisource thermal model is revised for relativistic and quantum situations. It is shown that the quantum effect can be neglected due to a very small result. The distributions of particle momenta, momentum components, transverse momenta, kinetic energies, and velocities in both the classical and relativistic situations are presented to give comparisons.